Perancangan Ulang Standard Operating Procedure Seksi Stock Preparation III-V Sesuai Sandar ISO 9001:2015 di PT. Pabrik Kertas Indonesia - Stephanus Robert; Jani Rahardjo (Jurnal Titra, 2021)
This research was conducted to remake the Standard Operating Procedure and Working Instruction according to ISO 9001:2015 standard at PT. Pabrik Kertas Indonesia. PT. Pabrik Kertas Indonesia do not yet have ISO 9001:2015 certification. The remaking documents will be used to prepare for ISO 9001:2015 certification in the future. The remaking is done by conducting direct observation and interviews with the relevant operators. The results of observations and interviews are used as supporting data in making new Standard Operating Procedure and Working Instruction. The new draft of Standard Operating Procedure and Working Instruction are then evaluated and validated by the Deputy Head of Stock Preparation III-V Section and Deputy Head of Production Unit 2 Department. The Standard Operating Procedure and Wokring Instruction drafts that have been validated will be stored as written guidelines for the implementation of the production process. The results obtained are 4 Standard Operating Procedures documents and 9 Working Instruction documents.